IMPLICATURE TYPES IN ED SHEERAN’S SELECTED SONG LYRICS - Emor, Melisa; Ismail, Ismail (Journal of Language and Literature, 2025)
Pragmatics, a branch of linguistics, examines how context influences meaning in communication. This study applies H.P. Grice’s theory of implicature to explore how Ed Sheeran’s lyrics convey implicit meanings that deepen emotional impact and engage listeners. While modern music often carries rich emotional undertones, the subtle, implied meanings in lyrics are frequently overlooked. Recognizing these layers is key to understanding how language in music communicates complex feelings and experiences. The research aimed to identify and categorize conventional and conversational implicatures in five selected songs: The A Team, Bloodstream, Castle on the Hill, Photograph, and Salt Water. Using a qualitative approach, the study analyzed lyrical content in both auditory and visual formats, focusing on how context and shared knowledge influence interpretation. A total of 32 implicatures were identified 15 conventional and 17 conversational each contributing uniquely to the listener’s emotional and interpretive experience. These findings highlight Sheeran’s ability to encode meaning through culturally familiar expressions and subtle narrative cues, enhancing the depth and relatability of his music. This study contributes to both linguistic and music discourse by addressing a gap in research on implicature in popular music. It underscores the importance of pragmatic analysis in understanding artistic language and offers insights into how implicit communication shapes listener engagement and emotional connection.